Need Analysis of Android E-Module based on Problem Based Learning Integrated of Anti-Bullying - Winda Noprina; Dina Fitria Handayani; Dini Deswarni (CV. Pusdikra Mitra Jaya, 2022)
In the middle of the rapid development of the digital world, learning innovation must be maintained. However, the implemented innovations must be appropriate in order to fulfill the learning objectives. There are still several hurdles to attaining the learning objectives in the discussion text. In terms of learning outcomes, the discussion text receives a lower grade than the KKM. The highest group has an average of 60, whereas the lowest group has a maximum of 40. In addition, there are issues with regard to the allocation of learning time, the unwillingness of students to ask and answer questions, and the assessment component, particularly attitude assessment. Writing discussion texts that are intended to foster the 4C in students, namely creative thinking (creative thinking), critical thinking and problem solving (critical thinking and problem solving), communicating (communication), and collaborating (collaboration), has not been entirely accomplished. To address these issues, instructional materials and proper learning models are necessary. This research is a qualitative descriptive study with the ultimate objective of collecting the results of e-module needs analysis. Analyzing student characteristics, curriculum, and learning materials constitutes data-gathering activities. The following are the outcomes of the requirements analysis: (1) Students like teaching materials that can be accessed via Android. (2) Students believe it is crucial to include anti-bullying characters in teaching materials. (3) KI and KD in learning to write discussion texts are at cognitive levels C1, C2, and C4, the dimensions of conceptual knowledge and abstract skills at the conceptual level. According to the findings of the three analyses, it is necessary to build a PBL-based e-module that incorporates anti-bullying strategies.